Electromagnetic lattice "invisibility" of the resonance cubic crystal made of magnetodielectric spheres - Kozar, A. I. (O. S. Popov Odesa National Academy of Telecommunications, 2013)
A solution and analysis of a problem on phenomenon of electromagnetic lattice "invisibility" og the limited resonance cubic crystal made of spheres are presented. The obtained results may be used when developing the devices wherein stealth technologies are employed.
Keywords: magnetodielectric spheres; electromagneticinvisibility; resonance cubic crystal